PUBLIC POLICIES AND CREATING GOVERNMENT FOOD PROGRAMS: A FEW CONSIDERATIONS - Silva, Eliane Regina Francisco da [UNESP]; Hespanhol, Rosangela Aparecida de Medeiros [UNESP] (Univ Estadual Paulista Julio Mesquita Filho, 2019)
Public policies are the materialization of a political action in favour of interest group representatives. The central objective of this article is to point out the main operating groups for the construction of referential public policies for family agriculture since 1994, as well as government food programs available in Brazil since 1940 and their features. The methodological procedures were composed of bibliographic survey. There was observed the relevance of existing public policies, above all family farm and beneficiaries (e.g. people in a situation of food and nutritional vulnerability), to reflect changes that have occurred over the years regarding the specifics and different generations of the agents acting, just as the socioeconomic losses of PAA budget cuts, the limitation of the PNAE resources, and the non-compliance with the law, in some municipalities, covering the spot purchase of, at least 30%, of the purchase of foodstuffs from family agriculture.
Keywords: Public policies; Government programs; Family farming